2000
DOI: 10.5357/koubyou.67.201
|View full text |Cite
|
Sign up to set email alerts
|

Interchangeability of Resin Composites and Bonding Agents Based on bis-GMA or UDMA.

Abstract: Recently, dentin bonding systems have been released separately from the resin composites, because the adhesive systems have been quickly improved. Since the merit of each material should be effectively utilized for each clinical case, the bonding systems and resin composites produced by different manufacturers may be combined according to the clinical purpose. The current restorative resins are basically categorized into two groups according to the main resin monomer, bis-GMA or UDMA resins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Further, monomer interaction between flowable and condensable composites could not be a reason because two brands of condensable composites based on Bis-GMA showed little gap formation. A previous study reported that the bond strength between an adhesive, which was based on Bis-GMA or UDMA, and a resin composite, which was also based on Bis-GMA or UDMA, was not influenced by differences in the main monomer 44) . According to these results, therefore, another factor was probably responsible for the differences in the amount of gap formation.…”
Section: Discussionmentioning
confidence: 95%
“…Further, monomer interaction between flowable and condensable composites could not be a reason because two brands of condensable composites based on Bis-GMA showed little gap formation. A previous study reported that the bond strength between an adhesive, which was based on Bis-GMA or UDMA, and a resin composite, which was also based on Bis-GMA or UDMA, was not influenced by differences in the main monomer 44) . According to these results, therefore, another factor was probably responsible for the differences in the amount of gap formation.…”
Section: Discussionmentioning
confidence: 95%
“…Baracco et al 28) and Mine et al 29) used a fixed resin composite with several resin adhesive systems to examine the microtensile bond strength of those adhesive systems. Hashimoto et al 30) and Shinkai et al 31) found that the combinations with the resin composite restorative and the other manufacturer's adhesive system do not influence significantly the bond strength. The first layer was filled horizontally by each resin composite restorative to a 2.0 mm thickness from the cavity floor.…”
Section: Bonding Reliabilitymentioning
confidence: 99%
“…Hashimoto et al 27) determined the bonding strength for 10 combinations of 2 types of bonding agents with different primary monomers and 5 types of composite resins. They found the greatest strength for the combination of both containing Bis-GMA as a primary monomer.…”
Section: Effects Of Cyclic Impact Loadingmentioning
confidence: 99%
“…In the oral cavity, FRC is subjected to cyclic impact loads from occlusion as well as temperature changes when exposed to saliva, food, and drink, which can significantly affect the FRC in everyday life [27][28][29][30][31][32] . To eliminate these negative influences, studies on composite materials that achieve better coupling between glass fiber and resin as well as studies on optimal glass fiber designs for dental restorations are needed.…”
Section: Effects Of Temperature Changementioning
confidence: 99%